Sudan : Midyear Review of the 2004 Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents the midyear review of the 2004 Staff-Monitored Program (SMP) for Sudan. Policy performance in the first half of 2004 was broadly in line with the program. All quantitative benchmarks and most structural benchmarks were met. Real GDP growth has been stronger than anticipated under the program, but inflation pressures are rising. The current account deficit (cash basis) was 1 1\2 percent of GDP, better than programmed, owing to a broad-based rise in exports and high private transfers.